Podwieczorek bez mikrofonu. (Gdynia : [s.n.], 1947)
Afisz inf. o występach w lokalu San Francisco 27.04.1947 r.
Keywords: Kawiarnie -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- życie artystyczne